Effects of Weight Training with Aerobic Glycolysis System (CHO) Reference on Waist Circumference - Surdiniaty Ugelta; Tono Haryono; Upik Rahmi; Nina Sutresna; Asti Dewi Rahayu Fitrianingsih; Ahmad Zaeri Sya'rani (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2022)
Physical fitness or fitness center and gymnastics studio as a business event, to improve the quality of human life through community sports. Maintain, maintain, and improve health, by using the facilities and infrastructure offered at the fitness center such as free weight equipment, and weight training. The aim is to see the results of weight training (free weight) through the analysis of the aerobic glycolysis system (CHO) on waist circumference. The treatment was given weight training with a duration of one minute (1 minute), using isotonic contractions, performed with 3 repetitions of sets, each set resting 30 seconds. Does it have a significant effect on the waist circumference of the perpetrator? The research method uses a one-Group Pretest-Posttest design. Isotonic exercise affects waist circumference.